Modeling and simulation of paddy drying: a bibliometric analysis (Research, Society and Development, 2019)
Rice is one of the staple foods of the Brazilian and world population. As part of post-harvest processing, drying is a critical step as it can affect the chemical, physical and nutritional properties of the final product. In this sense, the objective of this research consisted in the realization of a bibliometric review on the use of modeling and simulation in the drying process of paddy, providing an overview of the progress achieved, aspects to be developed and opportunities. A quantitative analysis of the related publications found in the Web of Science database was carried out, followed by a qualitative analysis of the most relevant articles. The results demonstrated the evolution of the subject and a great potential to be explored, mainly in the application of these models in the control, automation of the systems and in the support to decision making in real and large scale processes.